PENGARUH BIAYA PENCEGAHAN DAN BIAYA PENILAIAN TERHADAP PRODUK CACAT (STUDI KASUS PADA PABRIK GULA PTP NUSANTARA XI) - NUGRAHA SURYANATA, BAYU Nugraha (Jurnal Akuntansi AKUNESA, 2013)
Perseroan Terbatas Perkebunan Nusantara XI is one of the companies thatoperate the 16 sugar factory. To find out the influence of quality cost consists ofthe cost of prevention and cost assessment of damaged product, authors can usethe cost reports on existing reports profit/loss. Research methods used arediskriptif quantitative methods. Variables used in this research are variable costsand variable quality of products that are defective. The results showed that therelationship between the cost of the defective product to quality. The influence ofother variables outside of the regression model.Keywords: Cost of Quality, A defective product.